A PRELIMINARY QUALITATIVE STUDY OF AN ALKALOID IN THE FRUIT OF TERONG BELANDA (Cyphomandra betacea, Cav) - Fredryk Mandey; Mikael Dominggus; Tjodi Harlim (Universitas Gadjah Mada, 2003)
Preliminary studies on Terong Belanda (C. betacea ) have been carried out in this investigation with an aim to examine the presence of an alkaloid in the fruit of Terong Belanda. Several protocols had been done including maceration, extraction, evaporation, separation under column chromatography, crystallization and recrystallization, and testing with series of alkaloid reagent test. Finally one fraction, fraction D, obtaining in white sharp crystals, 96 mg, m.p 117.5 ºC gave positive results to an alkaloid especially from the group of atropine.